2012 IEEE International Conference on Mechatronics and Automation 2012
DOI: 10.1109/icma.2012.6282838
|View full text |Cite
|
Sign up to set email alerts
|

A memetic approach to the inverse kinematics problem

Abstract: Solving the inverse kinematics problem is at the core of the kinematics control of any articulated mechanism. It refers to determine the joint configuration that places the end-effector in an arbitrary position and orientation in the workspace. Kinematic inversion algorithms are generally based on the (pseudo)inverse Jacobian matrix, however, these methods are local and unstable in the vicinity of singular joint configurations. Alternatively, the inverse kinematics can be formulated as a constrained minimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Gonzalez and Blanco [9] demonstrated that a memetic approach increases the converge of the differential evolution algorithm for the inverse kinematic problem. They introduced a local search mechanism called discarding.…”
Section: Differential Evolution (De)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalez and Blanco [9] demonstrated that a memetic approach increases the converge of the differential evolution algorithm for the inverse kinematic problem. They introduced a local search mechanism called discarding.…”
Section: Differential Evolution (De)mentioning
confidence: 99%
“…Existing numerical methods on evolutionary algorithms, to name a few genetic algorithm [7], [8] and differential evolution [9], [10] provide solutions for the problems of exhaustive search with acceptable accuracy. In practice, usually manually designed look-up tables based approximate inverse kinematics based solutions are used for controlling a robotic manipulator [11].…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, in addition to obtaining a solution close to the optimum, it is necessary to generate it in a given time, which, in turn, implies the fast convergence of the algorithm. For this reason, the authors in [11] proposed a modification to DE in order to reduce the required time for finding the IK of a robot with 3-DOF, introducing a local search mechanism that they called discarding. Memetic algorithms [12][13][14], are hybrid methods that take advantage of the synergy from the combination of the global search capacity of some technique and the power of the local search of another mechanism.…”
Section: Introductionmentioning
confidence: 99%